The Crime of Insult: Legal Regulation and Language Analysis of Insult in Court Judgements - Randjelovic, Visnja M; Jelena, (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The importance of criminal law protection of honor and reputation and imprecise legal conceptual determination of insult, as a basic and general criminal offense against honor and reputation, pointed to the need to determine in theory and court practice the parameters that will help the courts when deciding whether in the particular case the criminal offense of insult exists or not. On this occasion, an objective criterion is applied, according to which an insulting statement is assessed from the aspect of existing customary, moral, and other norms in specific time and space. The variability of the concept of honor, which often changes its content and scope, also creates the need for language analysis of the degrading statements, which can sometimes be helpful in assessing whether in a particular case there is a criminal offense of insult or not. Connecting law with linguistics provides an interdisciplinary overview of the relationship of language, style, and composition of legal documents and their conditionality by specifics of individual fields of law. The attitude to the use of language which exists in legal theory and practice is significant and worth studying, and in the focus of interdisciplinary contribution to this issue, there is a criminal law overview of the use of language tools in criminal offenses against honor and reputation.
Keywords: honor, reputation, criminal law protection, insult, language analysis